3/2 fractional quantum Hall plateau in confined two-dimensional electron gas - Hailong Fu (Nature Portfolio, 2019)
Fractional quantum Hall states in 2D electron gases arise due to strong electron-electron interactions, which makes a general theoretical understanding difficult. Fu et al. present data showing the ν = 5/3 quantum Hall state has a 3/2 plateau in the diagonal resistance that has not been captured by existing models.